Bioprocessing of Coconut Shell, Coffee Grounds, and Peat Fiber Wastes for Renewable Energy Production: Rekayasa Bioproses Limbah Tempurung Kelapa, Ampas Kopi, dan Serat Gambut untuk Produksi Energi Terbarukan - Dhymas Sulistyono Putro; Andhira Trianingtyas; Rizki Auliansyah Putra; Bunga Resa Hartati; Radhiatunnisa S. Samad; Ryco Prawira Purba (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The increase in global energy demand and the accumulation of organic waste drive the need to utilize biomass as a renewable alternative energy. This study aims to evaluate the physicochemical characteristics, specifically moisture content and ash content, of biochar made from coconut shells, coffee grounds, and peat fiber based on the commercial briquette quality standard SNI 01-6235-2000. The methodological stages used include the carbonization (pyrolysis) process, particle size reduction, dough formulation using starch and lime binders, molding, and drying. The analysis results indicate that coffee grounds and coconut shells have the lowest average ash contents, successfully meeting the maximum SNI limit (≤8%) and making them highly feasible to be substituted as energy briquettes. Conversely, peat fiber produces a high ash content residue, making it less efficient as a fuel, but highly prospective to be repurposed as biochar (soil conditioner) in the agricultural sector. All initial biomass samples recorded a high moisture content, necessitating the optimization of post-molding thermal drying to meet the standard.